Selective Nerve Root Block in Treatment of Lumbar Radiculopathy: A Narrative Review - Jacqueline Chu Ruo Yang; Shi Ting Chiu; Jacob Yoong-Leong Oh; Arun-Kumar Kaliya-Perumal (Surgeries, 2022)
Selective Nerve Root Block (SNRB) is a precise local injection technique that can be utilised to target a particular inflamed nerve root causing lumbar radiculopathy for both diagnostic and therapeutic purposes. Usually, for SNRB to be therapeutic, a combination of a local anaesthetic agent and a steroid is injected under imaging guidance, whereas for diagnostic purposes, just the local anaesthetic agent is injected. While the ideal treatment strategy is to relieve the nerve root from its compressing pathology, local injection of steroids targeted at the affected nerve root can also be attempted to reduce inflammation and thus achieve pain relief. Although the general principle for administering an SNRB remains largely the same across the field, there are differences in techniques depending on the region and level of the spine that is targeted. Moreover, drug combinations utilised by clinicians vary based on preference. The proven benefits of SNRBs largely outweigh their risks, and the procedure is deemed safe and well tolerated in a majority of patients. In this narrative, we explore the existing literature and seek to provide a comprehensive understanding of SNRB as a treatment for lumbar radiculopathy, its indications, techniques, outcomes, and complications.